The Use Of Small Group Work Techniquesfor Improving Reading Comprehension - An Nisaa Rahmadani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The aims of this research were to find out (1) whether there was a significant difference in students’ reading comprehension abilitiesin terms of main idea, vocabulary, detailed information, and inferencesforstudents who weretaught using the Small Group Work (SGW) technique compared to those taughtthrough a standard technique. And (2) to find out if the use of the SGW technique motivated students studying reading comprehension to read more compared to other students.The samplefor this research was class VIII(1)and VIII(2) from the secondyearat SMPN 1Baitussalam in Aceh Besar in the academicyear 2014/2015. This research used true experimental design. The result of this study using the SGW technique showed that there wasno significant difference in the students’ reading comprehension in terms of the main idea.The use of the SGW technique did notmotivate and did not encouragethe experimental group students to develop their reading comprehension abilities.